2020
DOI: 10.3389/fcell.2020.584604
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis of the Regenerating Zebrafish Telencephalon Unravels a Resource With Key Pathways During Two Early Stages and Activation of Wnt/β-Catenin Signaling at the Early Wound Healing Stage

Abstract: Owing to its pronounced regenerative capacity in many tissues and organs, the zebrafish brain represents an ideal platform to understand the endogenous regeneration mechanisms that restore tissue integrity and function upon injury or disease. Although radial glial and neuronal cell populations have been characterized with respect to specific marker genes, comprehensive transcriptomic profiling of the regenerating telencephalon has not been conducted so far. Here, by processing the lesioned and unlesioned hemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
35
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 142 publications
(172 reference statements)
5
35
4
Order By: Relevance
“…Our findings on mRNA expression profiles are complementary to a recently published transcriptome study focusing on the immediate early changes in response to injury of the telencephalon (Demirci et al, 2020). Interestingly, this study reported activation of gene expression programs in both the injured and the uninjured hemispheres, even though the response was less pronounced and delayed in the injured hemisphere.…”
Section: Large Scale Response Of the Genome To Telencephalon Injurysupporting
confidence: 80%
“…Our findings on mRNA expression profiles are complementary to a recently published transcriptome study focusing on the immediate early changes in response to injury of the telencephalon (Demirci et al, 2020). Interestingly, this study reported activation of gene expression programs in both the injured and the uninjured hemispheres, even though the response was less pronounced and delayed in the injured hemisphere.…”
Section: Large Scale Response Of the Genome To Telencephalon Injurysupporting
confidence: 80%
“…The analysis of our sequencing data [14] with more than 600,000,000 Our findings on mRNA expression profiles are complementary to a recently published transcriptome study focusing on the immediate early changes in response to injury of the telencephalon [95]. Interestingly, this study reported activation of gene expression programs in both the injured and the uninjured hemispheres, even though the response was less pronounced and delayed in the injured hemisphere.…”
Section: Large Scale Response Of the Genome To Telencephalon Injurysupporting
confidence: 73%
“…We systematically analysed hundreds of transcription regulators for their expression in the injured telencephalon by in situ hybridisation on sections. We did not observe gene activation in the uninjured hemisphere [14,13,95]. Demirci et al [95] inflicted lesions by inserting a needle into the nostril.…”
Section: Large Scale Response Of the Genome To Telencephalon Injurycontrasting
confidence: 53%
See 2 more Smart Citations